Psychological Support for Family Caregivers of Patients With Amyotrophic Lateral Sclerosis at the Time of the Coronavirus Disease 2019 Pandemic: A Pilot Study Using a Telemedicine Approach - Sharbafshaaer, Minoo; Buonanno, Daniela; Passaniti, Carla; De Stefano, Manuela; Esposito, Sabrina; Canale, Fabrizio; D’Alvano, Giulia; Silvestro, Marcello; Russo, Antonio; Tedeschi, Gioacchino; Siciliano, Mattia; Trojsi, Francesca (Frontiers in Psychiatry, 2022)
The coronavirus disease 2019 (COVID-19) pandemic confined most of the population to homes worldwide, and then, a lot of amyotrophic lateral sclerosis (ALS) centers moved to telemedicine services to continue to assist both patients with ALS and their caregivers. This pilot, randomized, controlled study aimed to explore the potential role of psychological support interventions for family caregivers of patients with ALS through resilience-oriented sessions of group therapy during the COVID-19 pandemic. In total, 12 caregivers agreed to be remotely monitored by our center since March 2020 and underwent scales for global burden (i.e., Caregiver Burden Inventory, CBI), resilience (i.e., Connor Davidson Resilience Scale, CD-RISC), and perceived stress (i.e., Perceived Stress Scale, PSS) at two-time points (i.e., at pre-treatment assessment and after 9 months or at post-treatment assessment). They were randomized into two groups: the former group underwent resilience-oriented sessions of group therapy two times a month for 3 months, while the latter one was only remotely monitored. No significant differences were found in CBI, CD-RISC, and PSS during the 9-month observation period in the treated group compared with the control group, suggesting a trend toward stability of caregiver burden together with resilience and perceived stress scores in all the subjects monitored. The lack of differences in caregivers’ burden, resilience, and perceived stress scores by comparing the two groups monitored during 9 months could be due to the co-occurrence of the COVID-19 pandemic with the stressful events related to caring for patients with ALS that might have hindered the detection of significant benefits from short-lasting psychological support.